Ultrasonic doppler velocity profiler for fluid flow - Takeda, Yasushi (Fluid mechanics and its applications, 2012)
The ultrasonic velocity profile (UVP) method, first developed in medical engineering, is now widely used in clinical settings. The fluid mechanical basis of UVP was established in investigations by the author and his colleagues with work demonstrating that UVP is a powerful new tool in experimental fluid mechanics. There are diverse examples, ranging from problems in fundamental fluid dynamics to applied problems in mechanical, chemical, nuclear, and environmental engineering. In all these problems, the methodological principle in fluid mechanics was converted from point measurements to spatio-temporal measurements along a line. This book is the first monograph on UVP that offers comprehensive information about the method, its principles, its practice, and applied examples, and which serves both current and new users. Current users can confirm that their application configurations are correct, which will help them to improve the configurations so as to make them more efficient and effective. New users will become familiar with the method, to design applications on a physically correct basis for performing measurements accurately. Additionally, the appendix provides necessary practical information, such as acoustic properties.